The value of signs in social media accounts of #kelasblogger Instagram community - Salman; Rusadi, Udi; Nasrullah, Rully (Faculty of Communications Science, Dr. Soetomo University, 2022)
The use of communication technology is only limited to a means of exchanging messages. However, there is a significant value behind it. As Baudrillard points out, in a consumer society, people buy products based on sign value, as indicated in this case study. The results of this study indicate that the #Kelasblogger community's Instagram social media posts contain various values, such as commodity ​​and non-commodity values. The value of the commodity is detected in the XL Go MiFi modem purchased to support travelling activities. The use of information technology-based social media makes people have similar or uniform behaviour and compete in enjoying and spreading the sign values ​​in their lives. This consumptive behaviour is caused by several underlying factors, namely the development of lifestyle into a separate commodity, the shift from production to consumption, and capitalism's shift from labour exploration to consumer exploration.